Corruption Prevention in State Colleges and Universities - Santiago III, E F (KnE Social Sciences, 2018)
Corruption is everywhere and even government-run institutions of higher learning are not spared from such dilemma. Corruption inside State Universities and Colleges might be thought to be the small time or less impact problem in governance compared to other government entities amassing hard-earned people’s taxes, but the fact that schools are the second home of knowledge and values of an individual, therefore, graft and corruption values (inherited, observed or adapted) must first be cut within its grooming point. The study shall focus on how some government-run institutions of higher learning addressed the long standing deep rooted ill of society – corruption in their doorsteps. A review of policies and current practices in their fight of corruption of at least three to four government-run institutions of higher learning shall be showcased in this study. The results of the study shall be awareness and formalization of this infant field in Philippine Governance System and Public Administration encompassing different tools like internal auditing, systems studies, monitoring of government resources utilization, corruption prevention promotion and education drive, integrity systems check, corruption vulnerability assessments, red tape assessment, and the like. A conclusion formulated that corruption prevention should be embraced in all government entities especially in State Universities and Colleges, shifting from the old thought that we react after perpetrators of graft and corruption had amassed national wealth — preventing them doing such, by formulating ways to put in place integrity systems and promoting the culture of good governance for all time. Keywords: Anti-Corruption, Corruption Prevention, Integrity System, Good Governance, Public Administration